A XAFS study of the local environment and reactivity of Pt- sites in functionalized UiO-67 MOFs. (May 2016) - Borfecchia, E; Øien, S; Svelle, S; Mino, L; Braglia, L; Agostini, G; Gallo, E; Lomachenko, K A; Bordiga, S; Guda, A A; Soldatov, M A; Soldatov, A V; et al.
Abstract: We synthesized UiO-67 Metal Organic Frameworks (MOFs) functionalized with bpydcPt(II)Cl2 and bpydcPt(IV)Cl4 complexes (bpydc = bipyridine-dicarboxylate), as attractive candidates for the heterogenization of homogeneous catalytic reactions. Pt L3 -edge XAFS experiments allowed us to thoroughly characterize these materials, in the local environment of the Pt centers. XAFS studies evidenced the rich reactivity of UiO-67-Pt(II) MOFs, including reduction to bpydcPt(0) under H2 flow in the 600-700 K range, room-temperature oxidation to bpydcPt(IV)Br4 through oxidative addition of liquid Br2 and ligand exchange between 2 Cl - and even bulky ligands such as toluene-3, 4-dithiol. Preliminary XANES simulations with ADF code provide additional information on the oxidation state of Pt sites.